A gathering of days : a New England girl's journal, 1830-32 : a novel - Blos, Joan W. (New York : Aladdin Books, 1987)
The journal of a fourteen-year-old girl, kept the last year she lived on the family farm, records daily events in her small New Hampshire town, her father's remarriage, and the death of her best friend.
G8
Keywords: Diaries -- Fiction; New Hampshire -- Fiction